Antithrombotic therapy after myocardial infarction in patients with atrial fibrillation undergoing percutaneous coronary intervention. Issue 1 (6th November 2017) - Batra, Gorav; Friberg, Leif; Erlinge, David; James, Stefan; Jernberg, Tomas; Svennblad, Bodil; Wallentin, Lars; Oldgren, Jonas
Abstract: Aims: Optimal antithrombotic therapy after percutaneous coronary intervention (PCI) in patients with myocardial infarction (MI) and atrial fibrillation is uncertain. In this study, we compared antithrombotic regimes with regard to a composite cardiovascular outcome of all-cause mortality, MI or ischaemic stroke, and major bleeds. Methods and results: Patients between October 2005 and December 2012 were identified in Swedish registries, n = 7116. Landmark 0–90 and 91–365 days of outcome were evaluated with Cox-regressions, with dual antiplatelet therapy as reference. At discharge, 16.2% received triple therapy (aspirin, clopidogrel, and warfarin), 1.9% aspirin plus warfarin, 7.3% clopidogrel plus warfarin, and 60.8% dual antiplatelets. For cardiovascular outcome, adjusted hazard ratio with 95% confidence interval (HR) for triple therapy was 0.86 (0.70–1.07) for 0–90 days and 0.78 (0.58–1.05) for 91–365 days. A HR of 2.16 (1.48–3.13) and 1.61 (0.98–2.66) during 0–90 and 91–365 days, respectively, was observed for major bleeds. For aspirin plus warfarin, HR 0.82 (0.54–1.26) and 0.62 (0.48–0.79) was observed for cardiovascular outcome and 1.30 (0.60–2.85) and 1.01 (0.63–1.62) for major bleeds during 0–90 and 91–365 days, respectively. For clopidogrel plus warfarin, HR of 0.90 (0.68–1.19) and 0.68 (0.49–0.95) was observed for cardiovascular outcome and 1.28 (0.71–2.32) and 1.08 (0.57–2.04) for major bleeds during 0–90 and 91–365 days, respectively. Conclusion: Compared to dual antiplatelets, aspirin or clopidogrel plus warfarin therapy was associated with similar 0–90 days and lower 91–365 days of risk of the cardiovascular outcome, without higher risk of major bleeds. Triple therapy was associated with non-significant lower risk of cardiovascular outcome and higher risk of major bleeds.